You've Met Your Match: Using Culturally Relevant Pairing to Cultivate Mentoring Relationships during the Early Practicum Experience of Community College Preservice Teachers. Issue 4 (28th September 2020) - Garte, Rebecca; Kronen, Cara
Abstract: This work explores mentoring triad relationships between pre-service teachers, school-based cooperating teachers, and professors at a community college. Using cultural historical activity theory, we provide a retrospective analysis of the factors influencing the success of the mentoring relationships. We assessed 60 mentoring triads with a rubric focused on how triads established intersubjectivity and the activity systems of practicum and college course were able to intersect and establish common goals. Results showed that highly successful triads were most likely to have culturally matched student/cooperating teacher pairs and culturally diverse practicum placements. Qualitative analysis showed that an equal exchange of power among the triad was foundational for enabling intersubjectivity. Therefore, equal power exchange between the triad during early practicum experiences are supported by and support cultural responsiveness. We argue for further research on this population of pre-service teachers as well as greater attention to issues of power and cultural responsivity during mentorship.